Revealing the hopping mechanism of conduction in heavily doped silicon diodes - Borblik, V. L.; Shwarts, Yu. M.; Shwarts, M. M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Measurements of temperature dependences of excess tunnel current in heavily doped silicon p-n junction diodes at fixed values of the forward bias are carried out in liquid helium temperature region. In some voltage interval, these dependences are described well by the Mott law for variable range hopping conductivity. The interpretation of these results considers a p-n junction from a nontraditional point of view, namely, as heavily doped and highly compensated semiconductor.